Improving Fluent Reading Skills in Learning English Using the Demonstration Method for Grade III Students at Talitakum Private Elementary School - Windra Endriani Waruwu; Rahmawati Rahmawati; Ernita Daulay (RIRAI Publisher, 2023)
This study aims to improve the ability to read fluently in learning English, especially aspects of reading skills using the demonstration method for third grade students at Talitakum Private Elementary School. This type of research is pre-experimental research which only involves one class and is carried out in 2 meetings. Experimental units are conducted total sample which involved all grade III students. The results showed that: (1) student learning outcomes before being given treatment based on an average score reaching 33.3% were in the low category. Being in the high category, this can be concluded after being given treatment and obtaining a score of 83.3%. (2) Then, a figure of 76.9% is obtained for the average student involvement, which shows that students are active in their education. (3) The use of the demonstration model in this class is approved; this is shown by the positive response of students of 77.2%. Furthermore, it was found that the calculated t value was 4.5 with a frequency (df) of 22-1=21, this shows a significance level of 5%. This is in accordance with the t test procedure for carrying out inferential statistical analysis, as shown in t table 2. The null hypothesis (Ho) is rejected, and the alternative hypothesis (Hi) is accepted because t count > t table at the 5% significance level. Talitakum Private Elementary School has an increasing influence on the ability to read fluently in learning English using the demonstration method.